1997
DOI: 10.1093/ajcn/65.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of children with acute lymphoblastic leukemia: a longitudinal study

Abstract: To evaluate the nutritional consequences of acute lymphoblastic leukemia and its treatment, 15 children with leukemia were studied. Anthropometric data, fat-free mass by impedance, energy intake, and resting energy expenditure (REE) were determined at diagnosis and on days 22, 36, and 71 of the treatment. Interleukin (IL)-1 beta, IL-6, interferon-gamma, and tumor necrosis factor were also measured. Fifteen healthy control subjects were matched for age and sex. Body weight and height and body composition were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 14 publications
4
45
0
Order By: Relevance
“…Studies have confirmed the clinical impression that paediatric cancer patients undergoing chemotherapy have considerably lower oral energy and nutrient intakes than age-based recommendations [12,19,20,37]. A child under treatment may become at risk of malnutrition [29].…”
Section: Introductionmentioning
confidence: 85%
“…Studies have confirmed the clinical impression that paediatric cancer patients undergoing chemotherapy have considerably lower oral energy and nutrient intakes than age-based recommendations [12,19,20,37]. A child under treatment may become at risk of malnutrition [29].…”
Section: Introductionmentioning
confidence: 85%
“…23,24 Malnutrition is, however, a well recognized problem during treatment and is therefore generally considered to be a consequence of cancer therapy. 25 Assessment of nutritional status is diffi cult because there is currently no "gold standard" for assessment. In addition, nutritional status is multidimensional and can be assessed by methods that are anthropometric, biochemical, dietary, clinical and functional.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no evidence of unusually high energy intake in patients treated for ALL (Bond et al 1992;Delbecque-Boussard et al 1997;Reilly et al 1998). While testing hypotheses in relation to energy intake is limited by flaws in the methodology, these studies do not support the hypothesis that hyperphagia, induced by hypothalamic insult or corticosteroid effects (Tataranni et al 1996), is an important contributor to obesity in ALL.…”
Section: Energy Intakementioning
confidence: 96%